EMU: An Italian perspective - Masera, Rainer (PSL Quarterly Review, 2019)
The paper offers an Italian perspective on the creation and evolution of the European Economic and Monetary Union (EMU), which were and continue to be politically driven processes. European political leaders were responsible not for design defects but for a fundamental fault in execution: an original sin that continues to undermine the workings of the EMU. Contrary to commonly held beliefs, the Maastricht criteria and a rapid convergence process towards political union as the counterpart to the EMU were a viable framework. This consistent time path was not respected when the euro was created: the participation of Italy in 1999 and of Greece in 2001 did not satisfy the condition of prior fundamental convergence, notably in terms of public finance. The currency without a state, the lack of adjustment, and insufficient structural reforms imparted a deflationary bias, heightened the risks of the sovereign/bank nexus, and led to a wrong policy mix. In spite of significant steps to correct the system, current flaws continue to represent a major drawback to improving the resilience of the system. JEL codes: E42, E52, E61, F33, F34, F45, H63